Fiscal federalism and economic performance: New evidence from Switzerland - Heiko Tobias Burret; Lars P. Feld; Christoph A. Schaltegger (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2021)
The link between federalism and economic performance is still ambiguous. Aiming at clarification, we improve on a widespread shortcoming by measuring federalism not just by one variable but by various institutions that constitute it. To this end, Switzerland provides for a laboratory as its 26 cantons share a common framework, while the extent of federalism varies between the cantons and across time. By exploiting this setting, a two-way fixed-effects approach provides evidence for the expected heterogeneity: The impact of federalism on economic performance differs conditional on the federal instrument considered. Overall, instruments of competitive federalism appear to improve economic performance of the cantons, while for cooperative elements the effects are not unambiguously identified.
Keywords: H77; H73; O43; O47; 330; Fiscal Federalism; Economic Growth; Fiscal Competition; Fiscal Equalization